Effect of CFRP plate length on flexural behavior of GFRP reinforced concrete beam strengthening - Salleh, Norhafizah; Mohd Sam, Abdul Rahman; Mohd Yatim, Jamalludin; A. Khalid, Nur Hafizah; Abdul Hamid, Noor Azlina; Jamellodin, Zalipah; A. Majid, Masni (American Scientific Publishers, 2018)
This research investigates the effect of CFRP plate length on flexural behaviour of GFRP strengthened reinforced concrete beam. CFRP plate was placed on the bottom of the beam to act as tension reinforcement. Ten beams were tested, largely divided into over designed and under designed reinforced beams. Each group had one steel reinforced concrete beam, one GFRP reinforced concrete beam and three GFRP reinforced concrete beam with different length of CFRP plate at the bottom of beam. Tested parameters included flexural strength, stress–strain relationship and deflection. Results indicated that all strengthened beams had improved structural performance where the maximum flexural strength increased by 102% and maximum deflection reduced by 35%. The CFRP plate can significantly improve the load-bearing capacity of strengthened GFRP concrete beams.